Profil Penggunaan Obat Antibiotik di Apotek X Karanganyar - Pambudi, Risma Sakti Pambudi (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
A drug is a compound that is used to treat disease. Antibiotics from the hard drug class can be obtained using a prescription from a doctor. The availability of pharmaceutical preparations is important in supporting public health so it needs to be managed well. Therefore, it is necessary to know the profile of drug use as a basis for making drug plans. The aim of this research is to find out the percentage of antibiotic drug use in Karanganyar x pharmacies. This research method is included in the type of descriptive research with retrospective data collection based on stock card records and sales records and prescriptions at the Rizky Peni Farma Pharmacy. The samples in the study were all antibiotics sold in January-December 2023 at the Rizky Peni Farma Pharmacy. The results show that the use of 6 types of antibiotics at the Rizky Peni Farma pharmacy in the January-December 2023 period was used as a sample. In Antibiotic Sales, it was found that the three antibiotics that were frequently used were Cefadroxil 500 mg (42.92%), Amoxicillin (20.52%) and Metronidazole 500 mg (16.27%). Over a period of 12 months, Cefadroxil 500 mg was sold to 182 drugs, Amoxicilin to 87 drugs, and Metronidazole 500 mg to 69 drugs.